KEDUDUKAN HUKUM KREDITOR SEPARATIS DALAM PEMUNGUTAN SUARA PADA PENENTUAN PERDAMAIAN DI PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) (STUDI PUTUSAN MAHKAMAH KONSTITUSI REPUBLIK INDONESIA PERKARA NOMOR 015/PUU-III/2005) - Nurjannah Siregar; Sunarmi Sunarmi; Mahmul Siregar; Hasim Purba (Universitas Sumatera Utara, 2018)
ABSTRACT Separatist creditor is a holder of pawn, fiduciary collateral, hypothecation, or security right of other objects; he can execute his right as if there were no bankruptcy as it is stipulated in Article 55, paragraph (1) of Law No. 37/2004 on Bankruptcy and PKPU (Suspension of Debt Payment). This Article states that creditor can also request to PKPU which enables debtor to propose reconciliation for PKPU. However, in Article 228, paragraph (6) of Law No. 37/2004 on Bankruptcy and PKPU states that PKPU is not in effect for separatist creditor; the person in charge of determining debtor to get his right of PKPU is unsecured creditor, and it becomes one of the applicant’s propositions in requesting for Judicial Review of Law No. 37/2004 on Bankruptcy and PKPU on the 1945 Constitution. The result of the research showed that there werw inconsistencies in the regulation of Law No. 37/2004 on Bankruptcy and PKPU, againts setting legal domicile separatist creditor in voting to determine reconciliation in PKPU. This legal uncertainty of separatist creditor’s voting rights in determining reconciliation can cause the loss of separatist creditor’s right and status; he will get the lowest compensation of the value of collateral as it is stipulated in Article149 and Article 281, paragraph (2) of Law No. 37/2004 on Bankruptcy and PKPU which will probably be potential for the existence of fictitious creditors and collusion in the reconciliation plan. The Ruling of the Panel of Judges of the Constitutional Court of the Republic of Indonesia No. 015/PUU-III/2005 is considered not accurate and not objective since it does not consider any negative potentials which can occur in bankruptcy case when separatist creditor does not have any legal domicile in the voting for reconciliation in PKPU. Keywords: Separatist Creditor, Determining Reconciliation, PKPU (Suspension of Debt Payment)